THE CONCEPTUAL PAIR OF “KNOWLEDGEABILITY” AND “IGNORANCE” (KONFERENSIYA, 2026)
This article examines the conceptual domains of knowledgeability and ignorance, exploring the linguistic units that represent these notions, their role and significance in human life, and their spiritual foundations. The study argues that language functions not only as a tool for expressing this pair of opposing concepts but also as an important means of shaping their social, cultural, and personal significance.